2021
DOI: 10.1007/s12567-021-00369-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of a hollow cathode thruster: concepts, parameter study and initial test results

Abstract: Two electric propulsion concepts have been developed at Technische Universität Dresden as spin-off devices of regular hollow cathodes and initial testing has been conducted. Both devices represent millinewton thrusters that take advantage of thermionic electron emission using the low work function materials C12A7, LaB6, and thoriated tungsten in different design configurations. The first concept represents an electrothermal thruster which generates thrust by expanding and accelerating a heated propellant in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been reported to have some unique features, including a lower operating temperature, good chemical stability and reported iodine compatibility, as well as some specific failure modes [11,12]. Rand, McDonald and Drobny et al reported the overheating and melting of electride emitters during hollow cathode operation [6,11,13]. Kottke et al compared the thermionic emission properties of LaB 6 and C12A7.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to have some unique features, including a lower operating temperature, good chemical stability and reported iodine compatibility, as well as some specific failure modes [11,12]. Rand, McDonald and Drobny et al reported the overheating and melting of electride emitters during hollow cathode operation [6,11,13]. Kottke et al compared the thermionic emission properties of LaB 6 and C12A7.…”
Section: Introductionmentioning
confidence: 99%